Preliminary analysis of steelworks residues and their application in a sandy soil (Research, Society and Development, 2021)
The steel residues application (SR) in sandy soils, under a proper handling management, can result in a benefits range, among which, the soil acidity correction. This study investigated the gralunometric composition of three slags and one exhaustion powder from a steel mill, in the municipality of Marabá-PA, in addition to the ability of soil pH correction. To identify the granulometric fractions were used number 8, 10, 16 and 18 mesh sieves. The pH correction experiment were made in factorial scheme, evaluated 3 doses of each RS (1.5 t ha-1, 2.0 t ha-1 and 2.5 t ha-1) in vases with Neosol, for 60 days. Residues from the steel refining (EAFS, LDS and EAFD) showed a particle size predominantly under 1.00 mm, and promoted pH values above to 7.0. The blast furnace slag obtained domain of particle sizes > 2.00 mm, with 77% of the material retained in the sieves, and their soil disposition promoted similar results to dolomitic limestone, used traditionally to pH correction in acid soils, representing an alternative in soil preparation. Others residues also showed the soil pH correction capacity, although the used dosages proved to be above the ideal, with values above 7 and alkalinity tendency. The necessity of an investigation of EAFS, LDS and EAFD residues dosage are essential to pH soil correction, in order to condition the soil to pH ranges considered ideals (6-6.5).